Introduction to Information Visualization - Mazza, Riccardo; SpringerLink (Online service) (London : Springer London, 2009)
Information Visualization is a relatively young field that is acquiring more and more consensus in both academic and industrial environments. This concise introduction to the subject explores the use of computer-supported interactive graphical representations to explain data and amplify cognition. Written in a lively, yet rigorous, style the book explores ways of communicating ideas or facts about data, and shows how to validate hypotheses, and facilitate the discovery of new facts via exploration. The concepts outlined in the book are illustrated in a simple and thorough manner, building a reference for those situations in which graphic representation of information, generated and assisted by the use of computer tools, can help in visualizing ideas, data and concepts. With suggestions for setting communications systems based on, or availing of, graphic representations, this textbook illustrates cases, situations, tools and methods which help make the graphic representations of information effective and efficient.
to Visual Representations -- Creating Visual Representations -- Perception -- Multivariate Analysis -- Networks and Hierarchies -- WorldWideWeb -- Interactions -- Evaluations.
Keywords: Computer science; Computers; User interfaces (Computer systems).; Computer graphics; Computer Science; User Interfaces and Human Computer Interaction; Computer Imaging, Vision, Pattern Recognition and Graphics; Information Systems and Communication Service; Electronic books